'Running Fever': understanding runner identities in Shanghai through turning point narratives. Issue 2 (4th March 2018) - Ronkainen, Noora J.; Shuman, Amanda; Ding, Ting; You, Shilun; Xu, Lin
Abstract: Distance running has long been a popular leisure activity in many affluent countries, and it has recently become a fashionable sport in China. However, research into leisure running has mostly been confined to participants in the Global North. The present study explores runners' stories from Shanghai with a focus on psychological turning points – that is, subjectively important events that may change life trajectories and sense of self – within running careers. Thirty runners (14 women) participated in an interview using a life story approach. Turning point events were coded into six categories: relationship, transition in education/work, commitment, achievement, vulnerability and discovery. Stories were analysed for narrative themes and contexts, specifically in relation to running subculture and discourses surrounding gender and class. The findings highlight the relational achievement of a runner identity within the running subculture, emphasising 'right' attitude, persistence, and achievement. Simultaneously, the runner identity emerges as a signifier of a 'modern', middle class individual, who pursues self-development and credits oneself for accomplishments. Enthusiasm could, however, lead to injuries that challenged running identities. Runners in Shanghai share much of the narrative landscapes of running culture in the Global North, but also draw upon local narrative resources in runner identity construction.